Death and bereavement across cultures - Parkes, Colin Murray; Laungani, Pittu; Young, Bill, 1959- (London Routledge, 1997)
All societies have their own customs and beliefs surrounding death. This handbook explains how to offer appropriate and sensitive support to those from other cultures who are dying or bereaved
Introduction / Colin Murray Parkes, Pittu Laungani and Bill Young -- Culture and religion / Colin Murray Parkes, Pittu Laungani and Bill Young -- Grief in small-scale societies / Paul C. Rosenblatt -- Death in a Hindu family / Pittu Laungani -- A death on the roof of the world : the perspective of Tibetan Buddhism / Uwe P. Gielen -- Jewish views and customs on death / Ellen Levine -- Christianity / Harold Ter Blanche and Colin Murray Parkes -- The many facets of Islam : death, dying and disposal between orthodox rule and historical convention / Gerdien Jonker -- Secularization / Tony Walter -- Childhood, death and bereavement across cultures / Bill Young and Danai Papadatou -- Help for the dying and bereaved / Colin Murray Parkes -- Conclusions I : implications for practice and policy / Pittu Laungani -- Conclusions II : attachments and losses in cross-cultural perspective / Colin Murray Parkes
Includes bibliographical references (pages 244-251) and index
Keywords: Death -- Psychological aspects; Bereavement -- Psychological aspects; Death -- Cross-cultural studies; Bereavement -- Cross-cultural studies; Mourning customs; Bereavement; Grief; Cross-cultural studies